Liver abscesses with venous extension - rare complication of a common problem - Lal, Hira; Thakral, Anuj; Sharma, Manohar Lal; Kumar, Tarun (Turkish Journal of Gastroenterology, 2014)
Abstract Considering the high incidence of amoebic and pyogenic liver abscess in the developing world, occurrence of inferior vena cava thrombosis secondary to liver abscess is a rare but life threatening complication. We report 4 such complicated cases of liver abscess(s). The first case involved a large caudate lobe abscess extending across middle hepatic vein into suprahepatic inferior vena cava (IVC). Development of a left hepatic artery pseudoaneurysm following attempted percutaneous aspiration highlights the difficulties encountered in percutaneous interventional management of caudate lobe abscesses. The second case involved multiple liver abscesses with large thrombus in the right ventricular cavity & right ventricular outflow tract. The patient developed cardiorespiratory arrest limiting any aggressive management options for the complex nature of illness. The third case had a large caudate lobe abscess with direct extension into Intrahepatic IVC while the fourth showed a segment 4 abscess with thrombosis of adjacent left hepatic vein. These cases highlight the fact that diagnosis of such life threatening complications of liver abscesses as hepatic vein & IVC thrombosis requires high clinical suspicion followed by targeted imaging. Image guided interventional therapy is a useful tool for management in cases of liver abscess. But, abscesses in precarious locations like caudate lobe are associated with higher risk of complications including pseudoaneurysm formation asking for a cautious approach to interventional therapy in such circumstances.